Pemilihan, Pemanfaatan dan Pengguna Media dalam Proses Pembelajaran - Linda Hodijah; Raihan Nurtsany; Ridha Nurjannah; Sherina Dwiyanti; Usep Setiawan (JURNAL EDUKASI NONFORMAL, 2022)
The writing contains about media in learning as a component in learning activities that can prove success in learning. There are several things discussed in this paper including methods, selection criteria, and principles in selecting media. As well as the benefits of media in learning activities.